Binary Mutual Diffusion Coefficients of Isoniazid Aqueous Solutions at (298.15 and 310.15) K - Ribeiro, Ana C. F. (2009)
Binary mutual diffusion coefficients measured by the Taylor dispersion method in two different laboratories (University of Naples, Federico II, Italy, and University of Coimbra, Portugal) are reported for aqueous solutions of isoniazid at concentrations from (0.000 to 0.100) mol·dm−3 and at two temperatures (298.15 and 310.15) K. The hydrodynamic radii for the isoniazid in aqueous solution are calculated from the experimental results. In addition, the Hartley equation and the experimental diffusion coefficients are used to estimate activity coefficients for aqueous isoniazid at both temperatures